Pengembangan Aplikasi Monitoring Anak Berkebutuhan Khusus di Sekolah Luar Biasa Menggunakan Metode User Centered Design (UCD) - Rifki Adhitama; Ariq Cahya Wardhana; Gracia Rizka Pasfica; Yolanda Al Hidayah Pasaribu (Journal of Computer System and Informatics (JoSYC), 2022)
Special School B (SLB B) Yakut Purwokerto is an extraordinary school that focuses on handling Deaf Children with Special Needs (ABK) under the auspices of the Tama Business Welfare Foundation (YAKUT). In the process of monitoring student progress for guardians, SLB B Yakut Purwokerto still uses manuals and serves individual guardians. This is of course very ineffective and efficient. In addition, teachers also use social media in the form of WhatsApp to contact students' parents when students have finished learning activities at school. The development of technology is currently very rapid and it is appropriate for SLB B Yakut Purwokerto to develop monitoring activities using an effective and efficient system. Based on a review of several previous studies, User Centered Design (UCD) is an effective and most frequently used method to build an application. In understanding the user's cognition, character, and attitude, the design of the monitoring application for SLB B YAKUT Purwokerto students must focus on the user by applying the User Centered Design (UCD) method so that the application seems more interactive. The collection of user needs is carried out using three ways, including observation, interviews, and collecting the required documents. There are 5 stages that must be passed to implement the UCD method, plan the human-centered process, specifically the context of use, specify user and organizational requirements, product design solutions, and evaluate design against user requirements. The result of this research is that the design of the SoBat Yakut Monitoring System application design has been successfully completed to the prototype stage.